Vivencias de la enfermera en el cuidado de pacientes con tuberculosis - Barron Viloche, Elisa Karen (2010)
This qualitative research, was intended to reveal the phenomenon of the experiences of nurses in the care of patients with tuberculosis in health posts and centers belonging to Red Micro El Porvenir, being looked for to describe and to analyze the experiences of nurse and make your daily practice, a means for continuous improvement of the profession, raising the caution in patients with tuberculosis. The method used was qualitative - phenomenological, Waldow and Hurssel the authors who provided the theoretical support to the study. The stage of the investigation was in schools and health posts in the Micro Red El Porvenir, and the population consisted of nurses in charge of the Strategy for Prevention and Control of Tuberculosis; the sample size was determined by the saturation ¨snowball¨, method using semi-structured interviews. The information obtained was analyzed through the moments of the phenomenological path (description, reduction and phenomenological understanding) and finally the analysis Ideographic - Nemotético; identified nine categories that reveal the phenomenon: personal satisfaction, dedication, perseverance, empathy, family support, knowing the patient with tuberculosis, impotence, stigma and fear of failure